2009
DOI: 10.1016/j.jvs.2009.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes after Angioplasty of Isolated, Below-the-knee Arteries in Diabetic Patients with Critical Limb Ischaemia

Abstract: Surg 2009;xx:xx-xx.Background: It has been shown that concomitant percutaneous transluminal angioplasty (PTA) of above-the-knee (ATK) and below-the-knee (BTK) arteries is highly beneficial for limb salvage in patients with critical limb ischaemia (CLI), but few published studies have specifically investigated outcomes in diabetic patients with CLI associated with isolated small BTK-vessel disease. This study aimed to evaluate the long-term results of successful PTA for limb salvage in such patients.Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 0 publications
3
17
1
3
Order By: Relevance
“…Our results are in line with those of Ferraresi et al [30]. At a mean follow-up of 17.5 ± 12 months, we observed a limb salvage rate of 87 %, a major amputation rate of 9.4 %, and a mortality rate of 3.5 %.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results are in line with those of Ferraresi et al [30]. At a mean follow-up of 17.5 ± 12 months, we observed a limb salvage rate of 87 %, a major amputation rate of 9.4 %, and a mortality rate of 3.5 %.…”
Section: Discussionsupporting
confidence: 92%
“…In our experience, endovascular treatment of the BTK area therefore gives satisfactory results, and in agreement with studies reported in the literature [30], we believe that the PTA of these vessels decisively contributes to the treatment of CLI in diabetic patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations